2022
DOI: 10.1113/jp282725
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and exercise‐induced activation of AMPK as emerging therapies for myotonic dystrophy type 1 patients

Abstract: Myotonic dystrophy type 1 (DM1) is a multisystemic disorder with variable clinical features. Currently, there is no cure or effective treatment for DM1. The disease is caused by an expansion of CUG repeats in the 3′ UTR of DMPK mRNAs. Mutant DMPK mRNAs accumulate in nuclei as RNA foci and trigger an imbalance in the level and localization of RNA‐binding proteins causing the characteristic missplicing events that account for the varied DM1 symptoms, a disease mechanism referred to as RNA toxicity. In recent yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…BDNF, ANGPTL4, FGF21, LIF, and myostatin have all been shown to be dysregulated in DMD, whereas literature suggests AMPK activation may yield positive effects against the disease by contributing to increased muscle function and inducing mitophagy. Upregulated IL-6 signalling, reduced plasma irisin, and impaired AMPK signalling have all been associated with myotonic dystrophy ( Dozio et al, 2017 ; Nakamori et al, 2017 ; Ravel-Chapuis et al, 2022 ). Some studies have shown that AMPK activation reduced myotonia, inhibited RNA toxicity, and enabled functional benefits via histological improvements, and therefore suggested targeted activation of AMPK signalling as a potential therapeutic approach ( Brockhoff et al, 2017 ; Ravel-Chapuis et al, 2022 ; Ravel-Chapuis and Jasmin, 2022 ).…”
Section: The Ampk-myokine Relationship In Physiology and Pathophysiologymentioning
confidence: 99%
See 1 more Smart Citation
“…BDNF, ANGPTL4, FGF21, LIF, and myostatin have all been shown to be dysregulated in DMD, whereas literature suggests AMPK activation may yield positive effects against the disease by contributing to increased muscle function and inducing mitophagy. Upregulated IL-6 signalling, reduced plasma irisin, and impaired AMPK signalling have all been associated with myotonic dystrophy ( Dozio et al, 2017 ; Nakamori et al, 2017 ; Ravel-Chapuis et al, 2022 ). Some studies have shown that AMPK activation reduced myotonia, inhibited RNA toxicity, and enabled functional benefits via histological improvements, and therefore suggested targeted activation of AMPK signalling as a potential therapeutic approach ( Brockhoff et al, 2017 ; Ravel-Chapuis et al, 2022 ; Ravel-Chapuis and Jasmin, 2022 ).…”
Section: The Ampk-myokine Relationship In Physiology and Pathophysiologymentioning
confidence: 99%
“…Upregulated IL-6 signalling, reduced plasma irisin, and impaired AMPK signalling have all been associated with myotonic dystrophy ( Dozio et al, 2017 ; Nakamori et al, 2017 ; Ravel-Chapuis et al, 2022 ). Some studies have shown that AMPK activation reduced myotonia, inhibited RNA toxicity, and enabled functional benefits via histological improvements, and therefore suggested targeted activation of AMPK signalling as a potential therapeutic approach ( Brockhoff et al, 2017 ; Ravel-Chapuis et al, 2022 ; Ravel-Chapuis and Jasmin, 2022 ). As the full molecular mechanism of many of these pathways have yet to be elucidated, understanding myokine-AMPK interactions sheds some light on potential signalling pathways that may be leveraged in these investigations.…”
Section: The Ampk-myokine Relationship In Physiology and Pathophysiologymentioning
confidence: 99%
“…In addition to their roles as splicing factors, these proteins have a myriad of functions in RNA processing and localization [ 11 ]. There is also experimental evidence for other mechanisms involving transcription factors, signaling such as the glycogen synthase kinase 3-beta (GSK-3β), AKT, AMPK, PKC, Tweak/Fn14, PI3K/AKT pathways, other RNA binding proteins (e.g., hnRNPA1 and MSI2), circular RNA generation, microRNAs, mitochondrial dysfunction, increased cellular senescence, and most recently, calcium channel dysfunction in conjunction with chloride channel dysfunction [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. However, the strongest evidence is for the loss of function of MBNL proteins due to binding to the mutant RNA and their sequestration in the RNA foci [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, interventions, such as exercise, designed to stimulate AMP-activated protein kinase (AMPK), are strong candidates to mitigate declines in muscular function and other clinical variables in several NMDs, including DM1. [21][22][23][24] AMPK is a master regulator of neuromuscular plasticity due, in part, to its regulatory roles in mitochondrial biology. 21 Indeed, a recent clinical trial demonstrated several physiological benefits in DM1 patients following 12 weeks of aerobic exercise training that was accompanied by augmented skeletal muscle mitochondrial content and respiration, as well as partially normalized expression of mitochondrial dynamics proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Several therapies are being investigated to combat DM1 onset and progression. For example, interventions, such as exercise, designed to stimulate AMP‐activated protein kinase (AMPK), are strong candidates to mitigate declines in muscular function and other clinical variables in several NMDs, including DM1 21–24 . AMPK is a master regulator of neuromuscular plasticity due, in part, to its regulatory roles in mitochondrial biology 21 .…”
Section: Introductionmentioning
confidence: 99%